Pengembangan Media Pembelajaran PowerPoint Interaktif pada Mata Pelajaran Bahasa Indonesia Siswa Kelas VI Sekolah Dasar - Makhtum, Rohiqim; Rodhiyah, Ainur; Purnomo, M. Bakhtiar; Ilaah, Rohmatul; Putri Andani, Mutiara Fadhilah; Istiqfaroh, Nurul; Enun Kharisma, Nanda Veruna (Journal of Contemporary Issues in Primary Education, 2025)
The use of appropriate learning media is one of the important components in creating an interesting learning atmosphere and according to the needs of students. But at this time there are still many teachers who still use monotonous learning media, thus making students feel bored quickly during the learning process. This study aims to determine the feasibility and practicality in the process of developing an Interactive PowerPoint learning media in Indonesian language subjects. This research uses the DDD-E model development type consisting of Decide, Design, Develop, and Evaluate. Data collection was obtained using observation sheets, validation instruments, and also student response questionnaires. The research data shows the feasibility level of interactive PowerPoint media according to material experts, which is very valid with a score of 88. The level of feasibility according to media experts is quite valid with a value of 79. The results of the student response questionnaire obtained 96.1% with a very practical category. The conclusion of this study is that the development of Interactive PowerPoint learning media is feasible and practical to use in learning activities in Indonesian language subjects for grade VI elementary school students.